Perancangan E-Katalog Produk Berbasis Android pada PT Samudera Jaya Benelli Menggunakan Metode User Centered Design (UCD) - Susana Lin (METIK JURNAL, 2020)
Technological developments encourage business actors to be more creative in their competition to provide the best services to their consumers. In the field of motor vehicle sales today, however, brochures are still widely used in introducing their products. In light of this, PT Samudera Jaya Benelli wants to have an android-based e-catalog that contains information on their motorbike products so that it will facilitate the process of delivering information to potential customers who visit the showroom. Additionally, the use of e-catalogs can help the company save on the cost of printing brochures and catalogs, which has been the common practice so far. Furthermore, the development of this e-catalog information system uses the User-Centered Designing (UCD) method. The purpose of using UCD is to produce applications that have high use value, which includes the convenience in the usage, management, and effectiveness of the application, as well as the compatibility of the application to users' needs. Therefore, it is expected that this Android-based (mobile) e-catalog application will be able to increase efficiency and provide convenience in displaying products in the form of a digital catalog that has a modern, complete, and simple appearance